The Anxiety In Sandra Brown's Charade: A Psychoanalytic Approach - Widayanti, Rini; , Drs. M.Thoyibi, M. S; , Dra. Mauly Halwat (2013)
The major problem of this study is how the major character escapes from the anxiety, resulted from un-handled problems she encounters. The aim of this study is to identify the relationship between the causes of anxiety and the way to escape from anxiety being faced by the major character, by means of structural and psychoanalytic analysis. The object of this study is Sandra Brown's Charade and it is focused on one of the major character, namely Catherine Delaney. This study uses library research. The primary data are taken from the novel itself, while the secondary data are taken from some criticism and information needed. The method of data analysis is descriptive and the study employs Sigmund Freud's psychoanalysis to answer the problem. The outcome of the study shows that the major character encounters the conflict of her mental condition. Then it develops to be her anxiety that is influencing her to do some ways to escape from her anxiety. Actually, these ways are the effective ways to overcome the problem. Surakarta